PENERAPAN GAMBAR ISYARAT UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN TEKS RECOUNT PADA SISWA KELAS VIII I SMP NEGERI 10 MALANG - KHOLISATUL KHOTIMAH (LANGUAGE : Jurnal Inovasi Pendidikan Bahasa dan Sastra, 2022)
This research is Classroom Action Research (CAR) which aims to solve students' problems in class. In the learning process, it was found that most students had difficulties in learning English due to the lack of mastery in reading comprehension, also due to lack of vocabulary mastery. From the test results, the average score of students is still very low, namely 64.3 and does not meet the standard KKM score. Lack of motivation to learn and use of inappropriate learning media. Therefore, this study aims to improve reading comprehension and increase students' learning motivation, especially in reading activities. The researcher applied the cue drawing technique to increase students' interest in reading comprehension activities. Especially on the ability to read and understand the recount text material. Gesture pictures were chosen by researchers for learning strategies because in junior high school age students are more interested in the use of pictures, therefore researchers use sign pictures as a learning strategy in improving reading comprehension skills. This research has 2 cycles. In cycle 1 there were 2 meetings and in cycle 2 there were 4 meetings. Each meeting students were given different reading texts and questions. The subjects involved in this study were 32 students of class VIII I at SMP Negeri 10 Malang. Data were collected using observation lists, daily journals and achievement tests. The researcher decided that the cue picture strategy was successful if it met two criteria (1) 87.5% of students could achieve a score of 75 and (2) 80% of them were actively involved in the learning process. The results showed that 93.10% of the 32 students scored above 80, which means students experienced a significant increase. The average value before being given the cue drawing strategy was 64.3. After the researcher applied the strategy, the average score of the students became 84. The researcher found that 90.14% of the 32 students were actively involved in the learning process. Picture cues can improve students' comprehension skills in reading comprehension activities and increase student involvement in the learning process. ABSTRAKPenelitian ini adalah Penelitian Tindakan Kelas (PTK) yang bertujuan untuk memecahkan masalah siswa di kelas. Dalam proses pembelajaran ditemukan sebagian besar siswa memiliki kesulitan dalam pembelajaran Bahasa Inggris dikarenakan kurangnya tingkat penguasaan dalam membaca pemahaman, juga disebabkan kurangnya penguasaan kosakata . Dari hasil test, nilai rata rata siswa masih sangat rendah yaitu 64.3 dan tidak memenuhi standart nilai KKM. Kurangnya motivasi belajar dan penggunaan media pembelajaran yang kurang tepat. Oleh karena itu, penelitian ini bertujuan untuk meningkatkan membaca pemahaman dan menambah motivasi belajar siswa terutama dalam kegiatan membaca.Peneliti menerapkan teknik gambar isyarat untuk meningkatkan minat siswa dalam kegiatan membaca pemahaman. Terutama pada kemampuan membaca pemahaman pada materi teks recount. Gambar isyarat dipilih oleh peneliti untuk strategi pembelajaran dikarenakandalam usia tingkat sekolah menengah pertama siswa lebih tertarik pada penggunaan gambar, maka dari itu peneliti menggunakan gambar isyarat sebagai strategi pembelajaran dalam meningkatkan kemampuan membaca pemahaman. Penelitian ini ada 2 siklus. Di siklus ke 1 ada 2 pertemuan dan di siklus ke 2 ada 4 pertemuan.Setiap pertemuan siswa diberikan teks bacaan dan soal yang berbeda.Subjek yang terlibat dalam penelitian ini adalah 32 siswa kelas VIII I di SMP Negeri 10 Malang. Data dikumpulkan dengan menggunakan, daftar observasi, jurnal harian dan tes pencapaian. Peneliti memutuskan bahwa strategi gambar isyarat berhasil jika memenuhi dua kriteria (1) 87.5% siswa dapat mencapai skor 75 dan (2) 80% dari mereka aktif terlibat dalam proses pembelajaran. Hasil penelitian menunjukka bahwa 93.10% dari 32 siswa mendapat skor diatas 80 yang berarti siswa mengalami peningkatan yang signifikan. Nilai rata- rata sebelum diberikan strategi gambar isyarat berada diangka 64.3. Setelah peneliti menerapkan strategi tersebut, nilai rata- rata siswa menjadi 84. Peneliti menemukan 90.14% dari 32 siswa aktif terlibat proses pembelajaran. Gambar isyarat dapat meningkatkan kemampuan pemahaman siswa pada kegiatan membaca pemahaman dan meningkatakna keterlibatan siswa dalam proses belajar.